2009
DOI: 10.1111/j.1551-2916.2009.03232.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Kalsilite: A Simple and Economical Method

Abstract: This study reports a simple method to synthesize pure kalsilite (KAlSiO4) using readily available precursors, kaolinite and KOH solution, after only 12 h of hydrothermal treatment in mild conditions. A structural refinement has been carried out using the Rietveld method to obtain unit cell parameters, and the 29Si and 27Al magic angle spinning nuclear magnetic resonance spectra have shown the purity and complete Si/Al ordering of the kalsilite structure obtained. Finally, the morphology of the particles has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Becerro et al . previously reported that kalsilite has a high CTE for bonding to metals . Irma et al .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Becerro et al . previously reported that kalsilite has a high CTE for bonding to metals . Irma et al .…”
Section: Introductionmentioning
confidence: 95%
“…KAlSiO 4 is a feldspathoid with a structure of (Si, Al)O 4 tetrahedral framework . Kalsilite is a basic silicate mineral which can be used for PFM due to its high CTE and high flexural strength .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalsilite is a significant constituent in PFM and ceramic restoration systems [3]. It is used as the precursor of leucite [4]. Becerro et al [4] have previously reported that kalsilite being a high thermal expansion ceramic, is suitable for bonding to metals.…”
Section: Introductionmentioning
confidence: 99%
“…It is used as the precursor of leucite [4]. Becerro et al [4] have previously reported that kalsilite being a high thermal expansion ceramic, is suitable for bonding to metals. Kalsilite however crystallizes as a metastable phase when synthesizing leucite [5,6].…”
Section: Introductionmentioning
confidence: 99%